Strategi Pemilihan Supplier Bahan Baku dalam Mendukung Peningkatan Kinerja UMKM Bananas Food - Nida An Khofiyah; Juhaeni Juhaeni; Yusuf Irfan; Supriyati Supriyati; Hasyrani Windyatri (Yayasan Literasi Sains Indonesia, 2025)
Supplier selection is important in the production process, because raw materials greatly affect product results and production continuity. In Bananas Food Micro, Small and Medium Enterprises (MSMEs) located in Bekasi Regency, the main problem faced is that there is no mechanism or system for selecting the right raw material suppliers to meet production needs. Bananas Food MSMEs have also not implemented a method in supplier selection, so they have more than one supplier. This research was conducted using the Analytical Hierarchy Process (AHP) method. The criteria that are prioritized in supplier selection include availability, quality, and price and location. This study aims to determine the best supplier from several alternative suppliers. Based on the results of ranking the selection of banana raw material suppliers using the AHP method, determining supplier B as the best supplier for Bananas Food MSMEs with a weight value of 0.46, supplier C as the second alternative with a weight of 0.25, supplier D as the third alternative with a weight of 0.18, and supplier A as the fourth alternative with a weight of 0.11.